Pemekaran Daerah Wilayah di Tana Luwu Perspektif Kedatuan Luwu, Undang-Undang Nomor 9 Tahun 2015 dan Hukum Islam - Jabir, Riskal; Yusmad, Muammar Arafat; Arif, Firman Muhammad (Al-Mizan (e-Journal), 2024)
The purpose of this research is to find out the views and aspirations of the Kedatuan Luwu regarding the process of regional expansion that has an impact on the cultural and historical identity of the region, as well as evaluating the perceptions of the local government regarding Law Number 9 of 2015 and the implementation of regional expansion of Tana Luwu. This type of research is qualitative research with data collected through in-depth interviews with key informants such as local government, community leaders, academics, and related experts. In addition, data will also be obtained through document analysis and direct observation in the field. The results of the study show that: (1) the importance of regional expansion in Tana Luwu; (2) a comprehensive evaluation from various aspects, including political, economic, and cultural. The establishment of the Greater Luwu Province is considered necessary as a solution to overcome the problems that occur related to improving access to government services, more equitable infrastructure development, and more equitable distribution of resources.